Student Views on the Use of Online Student Response Systems: The Kahoot! Case - İlyas AKKUŞ; Uğur ÖZHAN; Hasan ÇAKIR (Anı Publishing, 2021)
Student response systems effectively collect and collate students' responses, allowing teachers to provide immediate feedback to learners, thereby preventing a decline in students' attention and motivation. In this study, a student response system instrument called Kahoot! was used. The study was conducted as a 4-week case study in an undergraduate course and a quiz consisting of 10 questions was created each week. Student views and recommendations were collected with an open-ended interview form. The obtained data were analyzed by content analysis, one of the qualitative analysis methods. The study findings were grouped under different codes, and it was determined that the majority of the students were of the view that the Kahoot! application improved course attendance, provided repetition of the learned topics, increased the motivation and attention. Furthermore, they stated as pre-service teachers that the Kahoot! Application should be used at the end of theoretical lectures and courses in the classroom and the number of questions should be increased.